An Elusive Gender Gap: Uncovering Gender Differences in Israeli and Palestinian Public Opinion - Siegel, Alexandra (Tufts Archival Research Center, 2014)
Over the past few decades, a growing body of public opinion research conducted in the United States and internationally has found that women are less supportive of the use of force and more likely to favor peaceful means of conflict resolution than men. Interestingly, the few studies that have explicitly explored gender differences in the context of the Israeli-Palestinian conflict have been at odds with this conventional wisdom. Most investigations of public opinion in Israel and Palestine have found little to no variation between male and female attitudes.I hypothesize that this discrepancy may arise because such studies of gender differences in Israel and Palestine have often neglected to analyze survey questions that ask respondents about theoretically gendered topics. I additionally posit that the heightened security threats faced by Israelis and Palestinians in their everyday lives may temper the gender gaps observed in other international contexts. Using a wide variety of survey data from 1988 to present, I test these hypotheses by analyzing gender differences in Israeli and Palestinian attitudes towards threat perception, the peace process, violence, and defense spending.The gender gaps that emerge in my findings are at odds with the conclusions drawn in past studies and demonstrate the important role that the gendered nature of threat perception plays in shaping Israeli and Palestinian attitudes towards the use of force. These findings have important theoretical implications for the study of gender and politics as well as key ramifications for the future of the Israeli-Palestinian peace process.